Padrões emergentes da montagem de comunidades de peixes e sua relação com fatores estruturadores, como a complexidade de habitat, invasão de espécies e processos temporais. - Cunha, Eduardo Ribeiro da (2017)
The set of processes underlying the community structure is often called assembly rules. Emerging patterns of the community assembly are used for theoretical and practical advances in ecology, allowing the advance of areas such as species responses to environmental progress. Analyses of emerging patterns were used to evaluate a fish assemblage structure in a Neotropical floodplain. These explanatory factors are related to the structural complexity offered by aquatic macrophytes, invasion processes and temporal variation in the structure of metacommunities. The relationships between a habitat complexity and patterns resulting from the community assembly of small fish in macrophyte stands (α and β diversity and co-occurrence among fish species) were investigated. In addition, the relationship between emergent patterns of the community assembly (components of diversity) in response to the invasion of a predatory fish species was also investigated. Moreover, patterns resulting from the community assembly of fish assemblages were used to investigate variation in metacommunity structure for this group of organisms. The main results related to the role of habitat complexity indicate a unimodal relationship of diversity and co-occurrence patterns among fish species with this explanatory variable. This indicates that complexity drives ecological processes related to how species respond to environmental conditions and how they respond to each other, which demonstrates that habitat complexity is an important driver of the structure of fish assemblages. Regarding the relationship between emergent patterns of the community assembly (components of diversity) in response to the invasion of a predatory fish, the results indicated that the resident fish community becomes nested with the introduction of the invader. This indicates that effects of the invasive predator are selective towards some species and, because some species can be extinguished, it is possible that ecological functions are lost throughout the invasion process. Regarding the temporal variation in the structure of metacommunities, the results found indicated that, for fish assemblages, metacommunity structure can vary among random and clumped species loss. This indicates that, during certain times, as species may respond to distinct factors and generate very complex or even random patterns of metacommunity structure, and, during other moments, certain groups of species are filtered out in a given environmental condition, which leads to clumped species loss. These structures varied along the short temporal scales, denoting a certain seasonality. In addition, the seasonal variation was distinguished along the large temporal scale, which indicates that the mechanisms driving seasonality of the metacommunity structure may change over time. In conclusion, general results allowed to infer about the potential effects of habitat structural complexity, invasion processes and seasonality on emerging patterns of the fish assemblage.